Cover Picture: Combining Topological and Steric Constraints for the Preparation of Heteroleptic Copper(I) Complexes (Chem. Eur. J. 38/2014). Issue 38 (15th September 2014) - Mohankumar, Meera; Monti, Filippo; Holler, Michel; Niess, Frédéric; Delavaux‐Nicot, Béatrice; Armaroli, Nicola; Sauvage, Jean‐Pierre; Nierengarten, Jean‐François
<x xml:space="preserve">Abstract</x> Cyclic to prevent the formation of bis‐phenanthroline copper(I) complexes but also too small to prevent the threading of the PP ligand: the combination of steric constraints with the topological restriction imposed by the macrocyclic phenanthroline ligand drives the complexation process and affords unprecedented heteroleptic CuI complexes with remarkable photophysical properties. For more details, see the Full Paper by B. Delavaux‐Nicot, N. Armaroli, J.‐P. Sauvage, J.‐F. Nierengarten et al. on p. 12083 ff.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>